Euclides da Cunha historiador: a reinvenção do bandeirante em Os sertões - Ferretti, Danilo Zioni (Revista de História, 2009)
This article discusses the historical aspect of Os sertões highlighting the relationship of Euclides da Cunha with the writing of São Paulo state history. Using Michel de Certeau's preoccupation with the social place of production of a historical text, this article analyzes the inclusion of Euclides da Cunha in the group of paulistanidade historians associated with the Historical Institute of São Paulo and his representation of the bandeirante in Os sertões.